2017
DOI: 10.1136/bmjopen-2016-012834
|View full text |Cite
|
Sign up to set email alerts
|

Computerised cognitive–behavioural therapy for depression in adolescents: feasibility results and 4-month outcomes of a UK randomised controlled trial

Abstract: ObjectivesComputer-administered cognitive–behavioural therapy (CCBT) may be a promising treatment for adolescents with depression, particularly due to its increased availability and accessibility. The feasibility of delivering a randomised controlled trial (RCT) comparing a CCBT program (Stressbusters) with an attention control (self-help websites) for adolescent depression was evaluated.DesignSingle centre RCT feasibility study.SettingThe trial was run within community and clinical settings in York, UK.Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 45 publications
(45 reference statements)
0
65
0
4
Order By: Relevance
“…The results also showed that the intervention was equally effective for boys and girls [35]. The findings of two studies showed that the decrease of depressive symptoms was larger in the participants in the unguided CBT condition when compared to the participants in the psychoeducational control condition [36,38]. Changes in mental health literacy after unguided computerized treatment were not reported.…”
Section: Intervention Effectsmentioning
confidence: 93%
See 2 more Smart Citations
“…The results also showed that the intervention was equally effective for boys and girls [35]. The findings of two studies showed that the decrease of depressive symptoms was larger in the participants in the unguided CBT condition when compared to the participants in the psychoeducational control condition [36,38]. Changes in mental health literacy after unguided computerized treatment were not reported.…”
Section: Intervention Effectsmentioning
confidence: 93%
“…Table 1 presents details of the included studies (k = 33). Sixteen studies were aimed at computerized treatments, of which nine were unguided computerized treatments (four computer-based and five internet-based) [30][31][32][33][34][35][36][37][38] and seven studies were guided computerized treatments (one computer-based and six internet-bases) [39][40][41][42][43][44][45], two studies at blended treatment [46,47], two studies compared unguided computerized, blended-and face-to-face treatment to no treatment [48,49], and eight studies were aimed at self-help internet-based games [50][51][52][53][54][55][56][57]. Furthermore, two studies that were focused on the use of an online monitoring tool aimed at registering and monitoring treatment progression [58,59] and three studies were aimed at characteristics of online interventions or studied the preferred modes of help seeking [60][61][62].…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the questionnaire has been extensively used worldwide in different populations with special health features, [22][23][24][25] and its metric properties have been described in its Spanish version for Spain, 6 as well as its comprehensibility and cultural adaptation in the general population. 7 In this regard, a pilot test was done in advance to assess the questionnaire's comprehensibility using query and paraphrasing methods in the target population, and it demonstrated an optimal comprehensibility.…”
Section: Instrumentsmentioning
confidence: 99%
“…Además, el uso de este cuestionario está muy extendido internacionalmente en diferentes poblaciones con características especiales de salud, [22][23][24][25] cuyas propiedades métricas han sido descritas en su versión española para España, 6 así como su comprensibilidad y adaptación cultural en población general. 7 En este sentido, se ha realizado previamente un estudio piloto para evaluar la comprensibilidad mediante métodos de indagación y parafraseo en la población objetivo y se ha presentado una óptima comprensibilidad.…”
Section: Instrumentosunclassified